Informal Learning and Entrepreneurial Success: A Longitudinal Study of Deliberate Practice among Small Business Owners. Issue 3 (14th December 2015) - Keith, Nina; Unger, Jens M.; Rauch, Andreas; Frese, Michael
Abstract : Informal learning activities are increasingly acknowledged as significant for learning and development in modern workplaces. Yet, systematic research on effects of informal learning on work‐related outcomes remains scarce. The present research focuses on deliberate practice—a construct from cognitive‐psychological expertise research that describes effortful practice activities specifically designed to improve one's performance. We propose that deliberate practice can be applied informally at work and, in the context of entrepreneurship, may contribute to entrepreneurial success. In a longitudinal study with 132 small business owners in Germany, we found partial support for the notion that success is increased in entrepreneurs who engage in self‐regulated and informal deliberate practice. In addition, deliberate practice interacted with environmental dynamism, indicating that deliberate practice pays off particularly in dynamic environments and may be detrimental in stable environments. This research not only informs entrepreneurial research as it sheds light on how entrepreneurs learn and develop their capabilities outside systematic training. It may also have broader implications for work and organisational psychology as self‐regulated deliberate practice may be a useful informal learning activity for a wider range of occupations and across work tasks, particularly those with rapidly changing work requirements.